Understanding the molecular bases behind congenital disorders of glycosylation - Oliveira, Tiago André Cunha (2023)
Congenital disorders of glycosylation (CDG) result from mutations affecting proteins involved in glycosylation pathways. Phosphomannomutase 2 (PMM2) deficiency (PMM2-CDG), the most common N-glycosylation disorder, induces hypoglycosylation of several proteins leading to multisystem involvement. This disease is related to a huge variety of mutante variants and a broad phenotypic spectrum, making genitype-phenotype correlations difficult. Mutations in PMM2 can affect is structure and function and may reveal a specific phenotype, One possible strategy for studying genotype-phenotype correlations would be to apply computational methods to assess the structural changes caused by amino acid substitutions. This would allow further development of personalised therapies for na untreatable disease. With the aim of developing na in silico protocol to analyse the impacto f diferente mutations on PMM2., several three-dimensional structures of mutated PMM2 were modelled and molecular Dynamics (MD) simulations were analysed to assess the impact of these variants at he energetic and molecular level on the normal activity of PMM2, including dimerization, folding, substrate-binding and structure-stability. The results predict the effect of missense mutations on the function of PMM2, in particular on the free energy of dimerization and folding of the protein.